Step-by-step self-assembled hybrids that feature control over energy and charge transfer - Grimm, Bruno; Schornbaum, Julia; Jasch, Hannelore; Trukhina, Olga; Wessendorf, Florian; Hirsch, Andreas; Torres, Tomas; Guldi, Dirk Michael (Proceedings of the National Academy of Sciences of the United States of America, 2012)
In the current work, we have documented the use of two complementary supramolecular motifs, namely multipoint hydrogen bonding and metal complexation, as a means to control the step-by- step assembly of a panchromatically absorbing and highly versatile solar energy conversion system. On one hand, two different perylenediimides (1a/1b) have been integrated together with a metalloporphyrin (2) by means of the Hamilton receptor/cyanuric acid hydrogen bonding motif into energy transduction systems 1a•2 or 1b•2. Steady-state and time-resolved measurements corroborated that upon selective photoexcitation of the perylenediimides (1a/1b), an energy transfer evolved from the singlet excited state of the perylenediimides (1a/1b) to that of the metalloporphyrin (2). On the other hand, fullerene (3) and metalloporphyrin (2) form the electron donor-acceptor system 2•3 via axial complexation. Photophysical measurements confirm that an electron transfer prevails from the singlet excited state of 2 to the elec-tron- accepting 3. The correspondingly formed radical ion pair state decays with a lifetime of 1.0 ± 0.1 ns. As a complement to the aforementioned, the energy transduction features of 1a•2 were combined with the electron donor-acceptor characteristics of 2•3 to afford 1a•2•3. To this end, time-resolved measurements reveal that the initially occurring energy-transfer interaction (53 ± 3 ps) between 1a/1b and 2 is followed by an electron transfer (12 ± 1 ps) from 2 to 3. From multiwavelength analyses, the lifetime of the radical ion pair state in 1a•2•3 - as a product of a cascade of light-induced energy and electron transfer - was derived as 3.8 ± 0.2 ns.